Micro Credentials and Global Classroom UMPSA s Borderless EdTech Endeavour to Empower Digital Learning - Amy Zulaikha, Mohd Ali; Nor Yazi, Khamis (UMPSA, 2024)
PEKAN, 1 August 2024 - The Centre of Instructional Resources & e-Learning (CIREL), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), hosted an inspiring University Teaching and Learning Innovation Carnival (UTLIC) Colloquium 2024 in Pekan yesterday, with the theme ‘Education without Borders: Empowering e-Learning through Micro-Credentials and Global Classroom’.